Assisting the Installation of Wireless Network Devices at Bina Tani Mulya Al-Muhajidin Boarding School - Usman Hanafi; Sutrisno Sutrisno; TB Utomo; Vitrasia Vitrasia; Enceng Sulaiman; Hertog Nugroho (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
The rapid development of Information and Communication Technology (ICT) can be utilized to improve the quality of services in the world of education. Bina Tani Mulya Al Mujahidin Foundation Boarding School Junior High School (YBTMA) previously did not have ICT infrastructure, especially hotspot or access point services. Based on this, it was necessary to provide assistance to design the installation of Microtik hotspot and access point devices, as well as human resource training to use and maintain these devices so that they could be utilized as much as possible. The installation of hotspot devices and access points was carried out on November 9, 2019, while the training was carried out on November 16-17 2019. This program received positive responses from the program recipients. Our strategy of deploying internet access supporting tools, which was then followed by a briefing of theory and practice, was well received.